Determinanty konkurencji jakościowej na rynku produktów spożywczych - Kijek, Tomasz (The Conditions of Quality Competition on Food Products Market, 2006)
The objective of the presented paper is to analyze the conditions of quality competition on food products market. The major forces that determine the quality competition include the following: greater technology of products manufacturing, threats to human safety and health, government regulation of quality and the rise of consumerism movement. Some conclusions concerning the conditions of quality competition in relation to customers and producers are drawn in the last part of the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 407-412